Avaliação da toxicidade e atividade antifúngica In Vitro do Timol sobre linhagens de Penicillium Citrinum - Dantas, Tassiana Barbosa (2017)
Fungi of the genus Penicillium can be found in various substrates and affect immunocompromised people, hospitalized patients, many animals and plants, as well as compromise the quality of air indoors. The indiscriminate use of antibiotics and the resulting framework of resistance of microorganisms to conventional antimicrobial therapy has been stimulating researchers to seek alternative sources of antimicrobial compounds, among them the medicinal plants and their phytochemicals. It is also known that natural products are not free from the possibility of toxic or adverse effects and, therefore, study their toxicity is fundamental. In this context, the present study evaluated the in vitro antifungal activity of seven phytochemicals (geraniol, thymol, carvacrol, citral, r-citronellal, s-citronellal, 7-hydroxy-citronellal, citronellal and isoeugenol) on 12 strains of Penicillium citrinum, by microdilution test, selecting the one that presented the best activity for the continuation of the tests. For the accomplishment of antioxidant activity and cytotoxicity studies human red blood cells obtained from the blood bank of the Lauro Wanderley University Hospital were used. The embryotoxicity study used embryonic cells of sea urchin (Echinometra lucunter). It was verified that thymol presented the best biological activity among the phytochemicals tested, inhibiting the growth of 100% of the strains at the concentration of 64 μg / mL (MIC) and showing fungicidal activity for 50% of the strains. The peracetic acid presented antifungal activity only in the concentration corresponding to the high level of disinfection proposed by the manufacturer, with MIC of 10,000 μg / mL. The antifungal standard presented MIC50 of 8 μg / mL and MIC90 corresponding to 256 μg / mL. Thymol presented CFM values similar to the MIC values for 1/4 of the strains, while voriconazole showed it for 1/6 of the strains. The antifungal effect of thymol and the control sanitizer was not due to the destabilization of the cell wall or to the complexation with the ergosterol of the plasma membrane. No additivity, synergism or antagonism were found resulting from the combination of timol-voriconazole, evaluated by the checkerboard method. Thymol showed good oral bioavailability and showed no mutagenic, tumorigenic or reproductive effects through in silico analysis. These data were confirmed by in vitro toxicity analyzes, which revealed: low erythrocyte cytotoxicity, with hemolysis values only for blood type O and below 5%; decreased erythrocyte damage caused by osmotic stress; significant antioxidant activity for B and O blood types; besides the absence of antimitotic activity in embryonic cells of sea urchin. These results suggest that thymol represents a new and promising possibility among products with antifungal activity against Penicillium citrinum, in addition to presenting significant antioxidant activity and some degree of protection of erythrocytes against osmotic stress.